A Computer-Aided Design Tool for Muqarnas - Dincer, Sevde Gulizar; Korumaz, Mustafa; Yazar, Tugrul (Assoc Computing Machinery, 2024)
In numerous instances of Islamic architecture, the geometric arrangement of muqarnas was established using square-rhombus tessellations in their flat projections. Similarly, in Turkiye, square-rhombus projection schemes have been employed in muqarnas designs since the era of the Anatolian Seljuks. This study introduces a computer-aided design (CAD) tool called Anatolian Muqarnas, which aims to recreate muqarnas schemes with square-rhombus projections. The tool is built upon a novel geometric analysis approach specifically tailored for Anatolian Seljuks muqarnas, drawing inspiration from Ammann-Beenker tiling and supertiles. Users of Anatolian Muqarnas can easily simulate existing or new designs by following predetermined rules. This contribution is expected to enhance discussions regarding the geometric analysis of muqarnas and the interplay between computing and cultural heritage at large.
Keywords: Muqarnas; Computer-Aided Design Tools; Tessellation; Architectural Geometry; Unity Game Engine; Patterns